Dog-type : amours de chiens, chiennes d’images et types ordinaires dans le daguerréotype américain - François Brunet (Transatlantica)
This article seeks to elucidate the phrase “dog-type” as applied colloquially to the daguerreotype in several American sources of the mid-19th century. After a glimpse at the photographic representation of animals in the medium’s first decades, I sketch out the role of the dog figure in American daguerreotype portraiture. This is followed by a close reading of a story published in 1849 by T.S. Arthur and the adjoining illustration, showing a “sitting” session at the daguerreotypist’s, and featuring in prominent position a dog. This dog seems to acknowledge the humiliation of his master by the process and thus to suggest a social interpretation of the daguerreotype portrait protocol. I conclude with a lexicological and contextual analysis of the phrase “dog-type” and its various possible meanings, whether satirical or not.